The Loss of a Generation: A Study on Children Whose Parents Were Victims of the COVID-19 Pandemic in Sleman, Yogyakarta - Sinuraya, Suci Iriani; Faidati, Nur (KnE Social Sciences, 2022)
The COVID-19 pandemic has impacted children’s living conditions and quality of life. The present qualitative study investigated the conditions of children whose parents were victims of COVID-19. The project was carried out from July to September 2021 in Sleman regency, Yogyakarta. Data were gathered through interviews, observations, and focus group discussions. At the time of the study there were 614 children in Sleman who had lost their parents. Our study revealed that the pandemic worsened the living conditions of children, particularly those whose parents passed away because of COVID-19. Children had feelings of a bleak future due to the loss of parents, were confused about how to survive and pay for living expenses and school fees, anxious about being abandoned by parents who had been their protectors, worried about their upbringing, and experienced feelings of loneliness and frustration. Hence, further actions need to be taken by both the government and social activists in order to deal with these problems. Based on the research findings, we present policy recommendations for stakeholders in order to deal with the children’s conditions. Keywords: COVID-19 pandemic, children, parents, loss of generation